Psychological distress in critically ill patients: Risk and protective factors - Gil-Juliá, Beatriz; Ferrándiz-Sellés, M. Desamparados; Giménez-García, Cristina; Castro-Calvo, Jesús; Ballester-Arnal, Rafael (Revista de Psicopatología y Psicología Clínica, 2020)
Abstract: Despite the importance of patients’ psychological well-being in their own recovery from illness, few studies examine these issues while the patient is still in ICU. This study analyzes the psychological distress of 71 ICU patients and the potential risk/protective factors for such distress. Patients showed moderate anxiety and depression although in a significant percentage clinical symptomatology was observed. More than halve of the patients revealed an intermediate general stress level and the most important stressor was having pain. Regarding risk factors for psychological distress, being a woman increased the risk for anxiety, depression and stress. Being a septic patient also increased the risk of experiencing stress. Conversely, some protective factors were being married and younger. These data provide a landscape of the distress experienced by patients while they are still in ICU, which is important to optimize the attention provided in a context where time for intervention is rather limited. Keywords: Critically ill patients; psychological distress; risk factors; protective factors. Afectación emocional en pacientes críticos: Factores de riesgo y de protección Resumen: A pesar de la importancia del bienestar psicológico del paciente en su recuperación, pocos estudios analizan estos aspectos mientras el paciente está todavía en UCI. Este estudio analiza la afectación emocional de 71 pacientes críticos y factores de riesgo/protección para dicha afectación. Los pacientes mostraron síntomas de ansiedad/depresión moderados, aunque un porcentaje significativo mostró sintomatología clínica. Más de la mitad de los pacientes reveló un nivel de estrés intermedio y el estresor más importante fue tener dolor. Asimismo, ser mujer aumentó el riesgo de ansiedad, depresión y estrés. Ser paciente séptico incrementó el riesgo de experimentar estrés. Por el contrario, algunos factores protectores fueron estar casado y ser más joven. Estos datos proporcionan un panorama general del malestar experimentado por los pacientes mientras están en UCI, lo cual es importante para optimizar la atención de los pacientes en un contexto en el que el tiempo para intervenir es bastante escaso. Palabras clave: Pacientes críticamente enfermos; malestar emocional; factores de riesgo; factores protectores.